Prevention techniques and effective management of diabetic foot: A literature review - Marques, Higor Goulart; Annoni, Gustavo Matge; Xavier, Henrique Souza; Júnior, Marcio da Silva lara; Ledur, Lucas Ortiz; Mattos, Leticia Rafaellen de; Artifon, Otavio Augusto Nesi; Velozo, Kennyel Andre; Pinculini, Ana Paula Gonçalves (Seven Editora, 2023)
In the context of diabetic foot, peripheral neuropathy plays a crucial role. The loss of sensitivity and muscle strength in the feet due to neuropathy increases the risk of ulcers. Additionally, peripheral vascular disease and immunodeficiency are risk factors, making diabetic patients more susceptible to complications. Diabetic foot prevention involves a multidisciplinary approach, including regular foot exams, self-care education, lifestyle changes such as quitting smoking, keeping the feet clean and dry, wearing appropriate socks and comfortable shoes. Local care, including ulcer debridement and the proper choice of dressings, is essential for healing. Negative pressure therapy may be an option in severe cases. Furthermore, other conditions, such as Charcot arthropathy, venous stasis, deep vein thrombosis, and fractures, can be confused with diabetic foot infections and require differentiation through medical history, physical examination, and imaging studies. In summary, diabetes mellitus is a global health concern, with serious complications like diabetic foot. Prevention, education, and proper treatment play fundamental roles in managing this condition. DOI:https://doi.org/10.56238/innovhealthknow-042